Evidence-Based Imaging Improving the Quality of Imaging in Patient Care - Medina, L. Santiago; Blackmore, C. Craig; Applegate, Kimberly (Springer New York : Imprint: Springer, 2011)
Evidence-Based Imaging: Quality Imaging in Patient Care, Revised Edition presents the radiologist and clinician with a user-friendly guide to the evidence-based science and the merit behind the diagnostic imaging performed in medicine. Edited by Drs. L. Santiago Medina, C. Craig Blackmore, and Kimberly E. Applegate, this ideal reference gathers contributions by internationally-renowned specialists in the field. The book provides a systematic framework for understanding the best imaging choices for patient care. Chapters highlight key points that support the clinical applications, allowing fast access to pertinent information. Topics include patient selection, imaging strategies, test performance, cost-effectiveness, and applicability. This Revised Edition adds ten new chapters to the material from the original, hardcover edition, covering radiation risk in medical imaging, the economic and regulatory impact of evidence-based imaging in the new healthcare reform environment in the United States, and new topics on common disorders. By offering a clear understanding of the science behind the evidence, the book fills a void for radiologists, clinicians, residents, and others with an interest in medical imaging and a desire to implement an evidence-based approach.